2019
DOI: 10.1016/j.accpm.2018.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative pain and post-operative nausea and vomiting (PONV) management after day-case surgery: The SFAR-OPERA national study

Abstract: Objectives: Since pain and postoperative nausea and vomiting (PONV) are the main reasons for failed discharge after day-case surgery, assessing pain and PONV is important. The aim was to describe the perioperative pain and PONV management within selected day-case surgical procedures in France. Methods: The OPERA trial was carried out on given days between December 2013 and December 2014. Each participating centre was required to fill out 3 separate questionnaires aiming at describing (1) protocols about pain a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 19 publications
0
28
0
Order By: Relevance
“…This may suggest that optimal monitoring should be begun from the evening of Day 0 to the evening of Day 3 (with systematic measurements morning, noon and evening) and at least one measurement per day from Day 3 onwards to optimize patient adherence. Interestingly, the peak of postoperative complications classically occured between Day 1 and Day 3 [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may suggest that optimal monitoring should be begun from the evening of Day 0 to the evening of Day 3 (with systematic measurements morning, noon and evening) and at least one measurement per day from Day 3 onwards to optimize patient adherence. Interestingly, the peak of postoperative complications classically occured between Day 1 and Day 3 [7].…”
Section: Discussionmentioning
confidence: 99%
“…[1,2]. However, safety and adverse events with these procedures remain debated in the literature with regard to potential medical or surgical complications at home [3][4][5][6][7]. Recently, digital technologies have been proposed to remotely monitor outpatients at home and in hospital in order to detect patients with early signs of disease progression or deterioration [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies [17,18] have shown that after day surgery nearly 80% of patients experience pain. Postoperative pain not only affects patients' rehabilitation and prolongs hospitalization, it can also result in progression from acute to chronic pain, which is the main cause of readmission after day surgery [19].…”
Section: Discussionmentioning
confidence: 99%
“…Written informed consent was obtained from all subjects participating in the trial. The trial was registered prior to patient enrollment at chictr.org.cn (ChiCTR-IOR-16010032, Principal investigator: Qulian Guo, Date of registration: 2016- [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26].…”
Section: Participantsmentioning
confidence: 99%
“…[1][2]. However, safety and adverse events with these procedures remain debated in the literature with regard to potential medical or surgical complications at home [3][4][5][6][7]. Recently, digital technologies have been proposed to remotely monitor outpatients at home and in hospital in order to detect patients with early signs of disease progression or deterioration [8][9][10].…”
Section: Introductionmentioning
confidence: 99%